We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
152
1
avatar

Given f(x)=2x^2−5x−3 and g(x)=2x^2+x .

What is (f/g)(x) ?

 Mar 11, 2019
 #1
avatar+105347 
0

(f / g) (x)   =   f(x) / g(x)  =

 

 2x^2 -5x - 3             (2x + 1) (x - 3)                 x - 3

____________  =    ____________   =        ______           { x not equal to 0 or -1/2 }

 2x^2  +  x                 x (2x + 1)                          x

 

 

cool cool cool {{

 Mar 11, 2019

9 Online Users